A blessing or a curse? The effect of market volatility on pairs trading profitability : Empirical evidence from Nasdaq 100 index constituents between 2007–2022 - Suokas, Markus (My University, 2023)
Pairs trading has been a highly profitable trading strategy used by hedge funds. The profitability of pairs trading has been decreasing, but an uptick in profitability has been observed during periods of market turmoil, such as the global financial crisis. This poses the question if pairs trading is only a suitable trading strategy during periods of high market volatility. Or can it still withstand as a strategy capable of yielding positive excess returns? The purpose of this thesis is to test a classical pairs trading strategy and to understand if such a strategy is still profitable. The other focus of this thesis regards market volatility and how it affects pairs trading profitability. The prenotion was that pairs trading should positively react to high market volatility, that is to yield higher returns during stressed market periods. The results of this thesis indicate that pairs trading does not yield statistically significant positive returns post the global financial crisis. The full period and the high volatility sub-periods have insignificant p-values. However, the low market volatility sub-period did yield positive and significant results, indicating that the pairs trading setup implemented in this thesis does work during low market volatility periods. This indicates the opposite effect that volatility has and that pairs trading should be implemented during level markets. Analyzing volatility and pairs trading more in detail, the volatility proxies derived from the VIX index were not found statistically significant. Multiple variations of the volatility index were tested to capture the monthly change in volatility and the overall volatility level.

Parikaupankäynnin on havaittu olevan yksi erittäin tuottoisa kaupankäyntistrategia, joita hedge rahastot ovat käyttäneet. Parikaupankäynnin tuotoissa on kuitenkin havaittu laskeva trendi, mutta kaupankäyntistrategiana se on tuottanut loistavasti erityisesti markkinakriisien aikana. On tärkeää ymmärtää, onko parikaupankäynti enää sopiva kaupankäyntistrategia vain kriisien aikana, vai tuottaako se vielä yleisesti ylituottoja? Tämän tutkielman tarkoituksena on tutkia yksinkertaista parikaupankäyntistrategiaa ja ymmärtää, onko se yhä kannattavaa. Toinen tämän tutkielman keskittymispisteistä on se, miten markkinavolatiliteetti vaikuttaa parikaupankäyntistrategian kannattavuuteen. Aikaisemman kirjallisuuden perusteella parikaupankäynti voidaan olettaa olevan kannattavampaa korkean markkinavolatiliteetin aikana. Tutkielman tulokset indikoivat, että parikaupankäynti ei tuota tilastollisesti merkitseviä positiivisia ylisuuria tuottoja aikakaudella 2008–2022. Sekä koko aikaperiodin että korkean volatiliteetin osakausien p-arvot eivät olleet tilastollisesti merkitseviä. Alhaisen markkinavolatiliteetin osakauden tuotot osoittautuivat kuitenkin merkittäviksi sekä positiivisiksi. Tämä tarkoittaa, että parikaupankäynti tämän tutkielman asetelmilla toimi parhaiten alhaisen volatiliteetin aikana. Tulos esittää vastakkaisen lopputuleman verrattuna aikaisempaan kirjallisuuteen, joka tarkoittaa, että parikaupankäyntiä tulisi toteuttaa tasaisten markkinaaikakausien aikana. VIX-markkinaindeksistä johdetut muuttujien ei löydetty olevan tilastollisesti merkitseviä. Indeksistä johdettiin monta eri muuttujaa, jotka mittasivat puhtaasti volatiliteetin kuukausittaista muutosta sekä yleistä volatiliteetin tasoa.
Keywords: pairs trading, volatility, market neutral, arbitrage